Los náufragos del Ciervo Volador: Una nueva mirada a la integración de extranjeros en el Perú virreinal - Donoso Bustamante, Sebastián (Pontificia Universidad Católica del Perú, 2025)
This work addresses a long-standing topic in Peruvian historiography: the presence of aliens in Peru during the 16th and 17th centuries. It also contributes to an understudied topic: the situation of those interned due to armed conflicts. In this regard, the wreck of the Dutch ship, Flying Deer, in the early 17th century offers a window into the treatment and temporary integration of foreigners in viceregal Peru. Contrary to their expectations, the twenty-three castaways were not treated as pirates or heretics, but as prisoners of war. Once catechized, they were able to work in Peru in areas related to the military and navy. Eleven of them were temporarily integrated into society but later returned to the United Provinces with useful intelligence for subsequent military expeditions. The study of this particular episode contributes to the historiography on the integration of foreigners in Peru. Thanks to their acceptance of Catholicism, they were able to stay temporarily in the country on a peaceful basis, a situation which they took advantage of to set up an United Provinces’ spy network in the Viceroyalty.

Este trabajo trata sobre un viejo tópico de la historiografía peruana, la presencia de extranjeros en Perú durante los siglos XVI y XVII, y aporta en un aspecto no estudiado: la situación de aquellos que eran internados por conflictos bélicos. En este sentido, el naufragio del navío neerlandés Ciervo Volador a inicios del siglo XVII representa una ventana para reflexionar acerca del tratamiento e integración temporal de extranjeros en el Perú virreinal. Contrariamente a sus expectativas, los veintitrés náufragos no fueron tratados como piratas ni herejes, sino como prisioneros de guerra. Una vez catequizados, pudieron trabajar en el país en áreas relacionadas con la milicia y la armada. Once de ellos se integraron temporalmente a la sociedad, pero luego regresaron a las Provincias Unidas con información de inteligencia útil para sucesivas expediciones militares. El estudio de este episodio particular contribuye a la historiografía sobre integración de extranjeros en Perú que, gracias a la aceptación del catolicismo, pudieron quedarse temporalmente en el país de forma pacífica, situación que fue por ellos aprovechada para constituir una red de espías de las Provincias Unidas en el Virreinato.
The shipwreck survivors of the Flying Deer A new look at the integration of foreigners in Viceregal Peru
Keywords: Aliens in the Viceroyalty; Captivity and social integration; Dirck Gerritsz; Adriaan Dircks; Flying Deer; United Provinces; Spies; Extranjeros en el Virreinato; Cautiverio e integración social; Dirck Gerritsz; Adriaan Dircks; Ciervo Volador; Provincias Unidas; Espías; https://purl.org/pe-repo/ocde/ford#6.01.01